The pattern of lung function tests in children with sickle cell disease: A case-control study. - Abinaya Kannan; Gaurav Sarnaik; Nikita Agarwal; Atul Jindal (PLoS ONE)
Background Sickle cell disease (SCD) is major inherited disease linked to a pro-inflammatory state, with a widespread involvement seen in all organ systems with lungs being no different. This research aims to analyze pulmonary function tests and fractional exhaled nitric oxide (FeNO) levels of children diagnosed with SCD and comparing them with healthy controls. Methods The study involved 100 children with SCD in stable state of health, without pain, crises, or acute illnesses for at least 1-month, and aged between 6-20 years and 100 age- and height-matched controls. Those with spinal deformities, acute or chronic cardiorespiratory symptoms, and cigarette smoking (in parents) were excluded. Measurements of forced vital capacity(FVC) and forced expiratory volume in one second(FEV1) were conducted using an automated single-breath vitalograph. FeNO was recorded using a hand-held device(NIOX MINO). Data werecollected and analyzed. Results Children with SCD had significantly lower pulmonary function values compared to controls: FEV1 median difference: 33.5% (95% CI: 27.2-38.0; p < 0.0001), FVC: 25.4% (95% CI: 30.0-32.25; p < 0.0001), FEV1/FVC: 0.088 (95% CI: 0.075-0.083; p < 0.0001), Peak Expiratory Flow Rate (PEFR): 24.8% (95% CI: 16.38-33.8; p < 0.0001), FeNO: 8.17 ppb (95% CI: 5.77-12.65; p < 0.0001). Pulmonary function test (PFT) abnormalities were associated with younger age (p = 0.0022). Age (p = 0.0011) was significantly associated with PFT severity, while blood transfusion frequency, and fractional exhaled nitric oxide (FeNO) levels were not. Increased weight (p = 0.001) and longer duration of hydroxyurea (p = 0.011) were associated with improved PFT severity (based on FEV1 z-scores). Conclusions Children with SCD often exhibit restrictive, obstructive, or mixed pulmonary function patterns. FeNO levels donot correlate with PFT severity.